2016
DOI: 10.1055/s-0036-1592133
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Antibiotic Management of Community-Acquired Pneumonia

Abstract: Community-acquired pneumonia (CAP) encompasses a broad spectrum of disease severity and may require outpatient, inpatient, or intensive care management. Successful treatment hinges on expedient delivery of appropriate antibiotic therapy tailored to both the likely offending pathogens and the severity of disease. This review summarizes key principles in starting treatment and provides recommended empiric therapy regimens for each site of care. In addition, we discuss the antimicrobial and anti-inflammatory role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…We used these protocols initially according to the degree of sepsis and clinical suspicion, after that antibiotics escalated depending on the results of the cultures and sensitivity of BAL and sputum. In concordance to our study, most of the guidelines recommend a combination therapy of a beta-lactam and macrolide or fluoroquinolone in those patients requiring ICU admission, and additional options are for possible pseudomonal infection [15], [16], [17], [18]. In our study, we found that BAL can detect up to 90% of pathogens responsible for the infection in the lower respiratory tract, while sputum can detect only 55% of organisms by culture.…”
Section: These Results Are In Concordance Withsupporting
confidence: 89%
“…We used these protocols initially according to the degree of sepsis and clinical suspicion, after that antibiotics escalated depending on the results of the cultures and sensitivity of BAL and sputum. In concordance to our study, most of the guidelines recommend a combination therapy of a beta-lactam and macrolide or fluoroquinolone in those patients requiring ICU admission, and additional options are for possible pseudomonal infection [15], [16], [17], [18]. In our study, we found that BAL can detect up to 90% of pathogens responsible for the infection in the lower respiratory tract, while sputum can detect only 55% of organisms by culture.…”
Section: These Results Are In Concordance Withsupporting
confidence: 89%
“…For inpatients with CAP, the IDSA/ATS guideline recommends the use of either a beta-lactam-macrolide combination or fluoroquinolone monotherapy for non-critically ill cases 15 ; the European and South African guidelines have the addition of a macrolide to the beta-lactam as an option 11 , 16 . Most of the guidelines recommend a combination therapy of a beta-lactam and macrolide or fluoroquinolone in those requiring ICU admission, and additional options are for possible pseudomonal infection 11 , 15 , 16 , 20 . The most controversial area has been whether the use of a macrolide antibiotic should be an obligatory component of initial antibiotic treatment 21 .…”
Section: Antibiotic Treatment Of Community-acquired Pneumoniamentioning
confidence: 99%
“…Earlier studies of hospitalized patients with moderately severe pneumonia suggested that beta-lactam monotherapy was not inferior to beta-lactam–macrolide combination therapy 22 , 23 . However, as has been indicated by several investigators, those studies had certain limitations that make it difficult to accept their conclusions 20 , 21 . A recent review highlighted all the studies documenting a benefit of combination therapy among inpatients; most of these studies were among CAP patients hospitalized in the ward and not the ICU 17 .…”
Section: Antibiotic Treatment Of Community-acquired Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations